SCREENING AND TREATMENT OF DIABETIC KIDNEY DISEASE IN TYPE 2 DIABETES MELLITUS (T2DM) PATIENTS: A CLINICAL AUDIT AT HOSPITAL SULTAN HAJI AHMAD SHAH TEMERLOH, MALAYSIA - Alagappa, Meenakshi; Shudim, Saiful Shahrizal; See, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Diabetic kidney disease (DKD) is a global health challenge that has garnered increasing attention due to its significant impact on individuals and healthcare systems worldwide. In Malaysia, DKD accounted for the majority of new dialysis patients, increasing cardiovascular risk and hence, escalating healthcare expenses. METHODOLOGY This clinical audit aims to assess the screening and treatment of DKD among T2DM patients in Hospital Sultan Haji Ahmad Shah (HOSHAS), Temerloh, Pahang. All T2DM patients attending the diabetes clinic in HOSHAS from June to July 2023 were included in this clinical audit. Electronic medical records were assessed for demographic data, blood pressure and glycaemic targets, screening and treatment of macro- or microalbuminuria. RESULTS We included 141 patients in this audit. Of those, 63.8% were females, with a mean age of 52.8 ± 15.0 years and an average duration of diabetes of 13.0 ± 8.4 years. The screening rate for albuminuria was high (93.6%) but only 25.5% of the patients had further quantification of albuminuria. Overall, 31.9% achieved a blood pressure target of below 140/80 mmHg but only 19.0% with albuminuria achieved a BP target of below 130/80 mmHg. A total of 19.1% of patients achieved HbA1c of less than 7%. Among the patients with albuminuria, 71.2% were on ACE-i/ARB and 39% were prescribed SGLT2 inhibitors. CONCLUSION This audit highlights the importance of early detection and appropriate management of DKD in T2DM patients. Microalbuminuria assessment, optimal blood pressure and renal-modulation therapy are essential in preventing the progression of albuminuria and reducing the risk of ESKD in patients with diabetes.